Smart Seed Dibber - Mohd Najib,; Mohamad, Mahmod Abdul Hakim; Hakimi, M. Izzul; Khamis, M. Naquib; Wagiman, Abdullah (Multidisciplinary Applied Research and Innovation, 2020)
Nowadays, there are many agriculture tools have been developed to help farmers implement various farming activities. However for small-medium farming scale there are still some difficulties faced by the farmers especially during seeding process.  Due to seeding machine are costly, most of the time this process need to be done by manual and cosuming a lot of time, energy and patient. In addition, the farmer could suffer back pain because seeding process require the person consistently bend down to ensure the seed is properly plant into the soil. Hence, in this project various concepts of dibber are compared in many aspects and parameters. Concept and parametric design is developed and analyzed according to the performance, structure construction and development costing. The aim of this tool’s design is to be able plant the seed without bend down, reduce time consumption and minimize required energy while using this dibber.  Also, this report contain explanation of the design and development of the mechanism, drawing analysis, material selection, fabrication process  and finally the data analysis through simulation.